A abordagem da responsabilidade social corporativa no Brasil pela mídia de negócios: um estudo longitudinal da Revista Exame - Ribeiro, Denise Queiroz (2020)
The construction of the meaning of Corporate Social Responsibility (CSR) influences the behavior of companies. And the business media proves to be an important arena where CSR understandings are deliberated, modified and disseminated. Much is discussed on the topic, but there is a scarcity of studies portraying the specificities of developing countries. This thesis contributes to expand studies on CSR in the Global South and aims to analyze the business media approach to CSR in Brazil. To this end, it identifies and characterizes the context in which CSR operates in Brazil to promote sustainable development; examines the arguments used by Exame Magazine to legitimize CSR in the light of the theoretical political perspective of CSR; and analyzes the scope of CSR in Brazil and contrasts the commitments by which companies are held accountable for the initiatives they have undertaken. A qualitative longitudinal study from the period 2000 to 2019 of Exame Magazine was carried out, through a critical content analysis of 395 pages of the Exame Guides to Good Corporate Citizenship and Sustainability. The results demonstrate the combination of rational technocratic and developmental arguments with moral arguments to justify CSR, which is then legitimized as a relevant form of conducting international relations and motivated by market demands and the need to guarantee the survival of companies in a scenario of poverty, social inequality and risk of scarcity of natural resources. The environmental agenda prevailed over the social one and the global agenda prevailed over the national one. Environmental development itself started to be valued as a business, with the ascension of the bioeconomy. Over the years, the CSR ideal has become more explicit, although the practices remained uncoupled from the community's demands. The understanding that the government is not able to meet the demands of society highlights the political nature of CSR in Brazil as an alternative to the government. Exame's approach showed inconsistencies and contradictions, such as failing to cover the environmental crimes of Brumadinho and Mariana caused by mining companies that were previously used by Exame as examples of socially responsible companies.